HUBUNGAN STROKE BERULANG TERHADAP STATUS FUNGSIONAL - Dede " Ismoyo; Wasisto " Utomo; Veny " Elita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Stroke is one of disease common caused of death world wide. Once stroke attacks it tends to get another  attack in forward. One of stroke effect is disability to do daily activity. The purpose of this research is to determine the correlation between recurrent stroke and functional status by using study comparative design and retrospective approach. The method of the research is purposive sampling for 30 respondents. The measurement is barthel index that consist of 10 scoring items related to ability and mobilization daily activities. The result is analized by univariat analysis that describes frequence distribution and bivariat analysis the used Wilcoxon. The result show us p value (0,00) < α (0,05). It show us that there is a correlation between reccurent stroke on functional  status. Based on this research, the reasercher suggest that the health personnel should give a special cure for the stroke people in order tonprevent a repeition stroke in forward.   Kata kunci            : Barthel index, functional status, recurrent stroke, stroke